The antidepressant-like activity of chiral xanthone derivatives may be mediated by 5-HT1A receptor and β-arrestin signalling. (December 2020) - Sałaciak, Kinga; Głuch-Lutwin, Monika; Siwek, Agata; Szafarz, Małgorzata; Kazek, Grzegorz; Bednarski, Marek; Nowiński, Leszek; Mitchell, Emma; Jastrzębska-Więsek, Magdalena; Partyka, Anna; Wesołowska, Anna; Kołaczkowski, Marcin; et al.
Background: Our previous studies showed that xanthone derivatives with N -(2-methoxyphenyl)piperazine fragment have an affinity to the 5-HT1A receptor and show antidepressant-like properties in rodents. In this study, we tested three xanthone derivatives, HBK-1 (R, S) and its enantiomers, in which we increased the distance between the piperazine and xanthone fragments by using a hydroxypropoxy linker. We hypothesized that this would increase the binding to the 5-HT1A receptor and consequently, pharmacological activity. Aims: We aimed to assess the in vitro and in vivo pharmacological activity of the xanthone derivatives. Methods: We evaluated the in vitro affinity for serotonin 5-HT1A and 5-HT2A receptors and serotonin transporter. We also determined the intrinsic activity at the 5-HT1A receptor. We investigated the antidepressant-like properties and safety after acute administration (dose range: 1.25–20 mg/kg) using the forced swim, tail suspension, locomotor activity, rotarod and chimney tests in mice. We also evaluated the basic pharmacokinetic parameters. Results: Our results indicated that the compounds showed a high affinity for the 5-HT1A receptor but very weak antagonistic properties in the Ca 2+ mobilization assay; however, they showed significant agonistic properties in the β-arrestin recruitment assay. In both behavioural tests the studied xanthone derivatives showed antidepressant-like activity. Pre-treatment with p-chlorophenylalanine or WAY-100635 abolished their antidepressant-like activity. None of the compounds caused motor impairments at antidepressant-like doses. The racemate penetrated the blood–brain barrier and had a relatively high bioavailability after intraperitoneal administration. Conclusions: Xanthone derivatives with N -(2-methoxyphenyl)piperazine fragment and hydroxypropoxy linker show increased binding to the 5-HT1A receptor and may represent an attractive putative treatment candidate for depression.